The Influence of Net Profit Margin, Return on Asset, Current Ratio, Price Earning Ratio, Solvency Ratio on Market Price - Ivena Mashoeda (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This study aims to analyze the influence of Profit Margin, Return on Assets, Current Ratio, Solvency Ratio on Market Price. Information about company share prices is related to these 5 variables. The data used in this research is the Consumer Good Industry Company (CGIC) which has complete data related to these variables so that the sample obtained is 13 companies in 2019-2022. The data analysis technique used in this research is the selection of a panel data regression model with the Chow test, Hausman test, large range multiplier (LM) test, and parameter significance test. The test results can be concluded that Net Profit Margin (NPM) has a significant effect on Market Price (MP) while Return on Assets (ROA), Current Ratio (CR), Price Earning Ratio (PER), Solvency Ratio (SR) do not have a significant effect on Market Price (MP).